(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2026)
The study investigated ethical standards as correlates of effective supervision for sustainable national development in secondary schools in Owerri Zone 1 of Imo State. Three null hypothesis tested at 0.05 level of significance guided the study. The population of the study comprised of all the teachers in Owerri Zone 1 totaling 2,328. A sample size of 200 teachers was drawn using the purposive and cluster sampling techniques. The instrument for data collection was a researcher developed questionnaire titled “Ethical Standards of Supervision Effectiveness (ESSSE). The instrument was validated by two specialists from the faculty of education Imo State University. Data obtained were analyzed using Pearson product moment correlation. The results showed that a significant relationship exist between ethical standards and supervision effectiveness. Based on the findings it was recommended that unethical conducts of supervisors should be avoided to gain the trust, confidence and respect of teachers during supervision